Carbon and Sulfur Cycling below the Chemocline in a Meromictic Lake and the Identification of a Novel Taxonomic Lineage in the FCB Superphylum, Candidatus Aegiribacteria - Hamilton, Trinity L.; Bovee, Roderick J.; Sattin, Sarah R.; Mohr, Wiebke; Gilhooly, William P.; Lyons, Timothy W.; Pearson, Ann; Macalady, Jennifer L. (Frontiers in Microbiology, 2016)
Mahoney Lake in British Columbia is an extreme meromictic system with unusually high levels of sulfate and sulfide present in the water column. As is common in strongly stratified lakes, Mahoney Lake hosts a dense, sulfide-oxidizing phototrophic microbial community where light reaches the chemocline. Below this ‘plate’, the euxinic hypolimnion is anoxic, eutrophic, saline, and rich in sulfide, polysulfides, elemental sulfur, and other sulfur intermediates. While much is known regarding microbial communities in sunlit portions of euxinic systems, the composition and genetic potential of organisms living at aphotic depths have rarely been studied. Metagenomic sequencing of samples from the hypolimnion and the underlying sediments of Mahoney Lake indicate that multiple taxa contribute to sulfate reduction below the chemocline and that the hypolimnion and sediments each support distinct populations of sulfate reducing bacteria (SRB) different from the SRB populations observed in the chemocline. After assembling and binning the metagenomic datasets, we recovered near-complete genomes of dominant populations, including two Deltaproteobacteria. One of the deltaproteobacterial genomes encoded a 16S rRNA sequence that was most closely related to the sulfur-disproportionating genus Dissulfuribacter and the other encoded a 16S rRNA sequence that was most closely related to the fatty acid- and aromatic acid-degrading genus Syntrophus. We also recovered two near-complete genomes of Firmicutes species. Analysis of concatenated ribosomal protein trees suggests these genomes are most closely related to extremely alkaliphilic genera Alkaliphilus and Dethiobacter. Our metagenomic data indicate that these Firmicutes contribute to carbon cycling below the chemocline. Lastly, we recovered a nearly complete genome from the sediment metagenome which represents a new genus within the FCB (Fibrobacteres, Chlorobi, Bacteroidetes) super phylum. Consistent with the geochemical data, we found little or no evidence for organisms capable of sulfide oxidation in the aphotic zone below the chemocline. Instead, comparison of functional genes below the chemocline are consistent with recovery of multiple populations capable of reducing oxidized sulfur. Our data support previous observations that at least some of the sulfide necessary to support the dense population of phototrophs in the chemocline is supplied from sulfate reduction in the hypolimnion and sediments. These studies provide key insights